2007
DOI: 10.1080/10942910601183643
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Germinated Brown Rice Substituted Bread: Dough Characteristics and Bread Structure

Abstract: Pre-germinated brown rice (PGBR) having the germ length of 0.5-1.0 mm is produced as a healthy food by immersing the brown rice in water. In this article, various additives were used for making PGBR breads, and suitable combinations of PGBR and additives for breadmaking were evaluated to provide PGBR bread with high functional properties. The 30% of the wheat flour was substituted with PGBR (PGBR 30), and combined additions of phytase (PHY), hemicellulase (HEM) and sucrose fatty acid ester (SE) to PGBR 30 impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In particular, the link between oxidative stress and many chronic diseases is widely acknowledged, and GBR could affect the course of such oxidative stress-related diseases. Already, there have been reports of successful incorporation of GBR into food products like bread, and consumer willingness to purchase the products is encouraging [9799]. Development of such products may bring closer the benefits of GBR to a wide range of people as suggested by Patil and Khan [17].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the link between oxidative stress and many chronic diseases is widely acknowledged, and GBR could affect the course of such oxidative stress-related diseases. Already, there have been reports of successful incorporation of GBR into food products like bread, and consumer willingness to purchase the products is encouraging [9799]. Development of such products may bring closer the benefits of GBR to a wide range of people as suggested by Patil and Khan [17].…”
Section: Discussionmentioning
confidence: 99%
“…The extrudated bread was shown to be sweeter and equivalently palatable as a result of the organoleptic test (Ohtsubo et al 2005). Morita et al (2007) used various additives for making GBR breads and evaluated suitable combinations of GBR and additives for bread making to provide GBR bread with high functional properties. The 30% of the wheat flour was substituted with GBR (GBR 30), and they found that combined additions of phytase (PHY), hemicellulase (HEM) and sucrose fatty acid ester (SE) to GBR 30 improved the bread qualities with more suitable dough properties as compared with sample without additives.…”
Section: Gbr and Extrusion Cookingmentioning
confidence: 99%
“…Recently, researches have focused on producing GBR by soaking method and improving GABA content in GBR (Suzuki and Maekawa 1999;Morita et al 2007). Saikasa et al 1994 described the accumulation characteristics of GABA in ten rice cultivars with water soaking.…”
Section: Introductionmentioning
confidence: 99%